Genetic variability for forage yield and nutritive quality characteristics in selected inbred x Triticosecale genotypes - Venter, Willem Daniel (University of the Free State, 2009)
The objective of this study was to study the combining ability, heritability and additive genetic correlation of various nutritive quality, forage yield and animal production characteristics in a selected fixed population of triticale genotypes. The vegetative matter obtained from two sequential cuts per plot was used for chemical analyses and the calculation of plant production and animal production. The trial was a split-plot in time experiment planted in a randomised block design. Three replications were planted and the plots were made up of three rows each. Characters measured for forage quality in both cuts were NDF, ADF, ADL, hemicellulose, crude cellulose, NDFadj, EE, NSC, IVDOM, ME and MRT. Characters used for plant production were kg DM/ha, crude cellulose yield/ha, EE yield/ha, NSC yield/ha, IVDOM yield/ha and ME yield/ha. Characters used for animal production were DM Intake/steer/day, ME Intake/steer/day, LWG/steer/day and Live weight gain/ha. Each one of the animal production characters were calculated according to three different feed intake models. Significant differences were shown in cut 1 between genotypes for NSC, EE and all fibre characters except hemicellulose and crude cellulose. Significant differences were shown in cut 2 for NSC, ME and MRT. Significant differences were shown in both cuts for all the plant production characters. Highly significant differences were shown in cut 1 for Live weight gain/ha according to all three different intake models. The F1 progeny of a 6 x 6 half diallel cross were evaluated in the combining ability analyses using the Method 4, mixed model B analysis of Griffing (1956b), because only one reading per plot was obtainable for each of the characteristics measured. In the combining ability analyses of the F1 progeny, significant differences were shown in cut 1 for gca effects of EE and all fibre characters except hemicellulose. Significant differences were shown in cut 2 for EE, IVDOM, ME and MRT. Significant differences were only shown in cut 1 for all the plant production characters. Highly significant differences were shown in cut 1 for Live weight gain/ha according to all three different intake models. The levels of relative high parent heterosis did not warrant the forming of hybrids in an effort to increase Live weight gain/ha. The σ2 gca/σ2 sca and h2n were moderately high for NDFadj, kg DM/ha and Live weight gain/ha in cut 1 and moderate for MRT in cut 2. Highly significant additive correlations were found between IVDOM yield/ha and Live weight gain/ha according to all three different intake models in cut 1. A significant negative additive genetic correlation was found between kg DM/ha in cut 1 and IVDOM in cut 2. Recommendations were given for the identification of breeding parents, selection in the early generations as well as the final evaluation in order to select a new cultivar for registration.

Die doel van hierdie studie was om die kombineervermoë, oorerflikhede en additiewe genetiese korrelasie van verskeie voedingswaarde-, voeropbrengs- en diereproduksie eienskappe in ‘n geselekteerde korog populasie te bepaal. Die plantmateriaal verkry vanaf twee opeenvolgende snysels per perseel is gebruik vir die chemise ontledings en die daaropvolgende berekenings van plantproduksieen diereproduksie eienskappe. Die proef was ‘n verdeelde perseel-in-tyd eksperiment wat geplant is volgens ‘n ewekansige blokontwerp. Drie herhalings is gebruik en elke perseel het uit drie rye bestaan. Voedingswaarde eienskappe wat in albei snysels bepaal is, was ‘NDF’, ‘ADF’, ‘ADL’, hemi-sellulose, ru-sellulose, ‘NDFadj’, ‘EE’, ‘NSC’, ‘IVDOM’, ‘ME’ en ‘MRT’. Eienskappe wat vir plantproduksie gebruik is, was kg DM/ha, ru-sellulose opbrengs/ha, ‘EE’ opbrengs/ha, ‘NSC’ opbrengs/ha, ‘IVDOM’ opbrengs/ha en ‘ME’ opbrengs/ha. Eienskappe wat vir diereproduksie gebruik is, was DM inname/dier/dag, ‘ME’ inname/dier/dag, lewende massatoename/dier/dag en lewende massatoename/ha. Elkeen van die diereproduksie eienskappe is volgens drie verskillende voedingsinname modelle bereken. Daar was betekenisvolle verskille tussen genotipes by snysel 1 vir ‘NSC’, ‘EE’ en al die veseleienskappe behalwe hemi-sellulose en ru-sellulose. Daar was ook betekenisvolle verskille by snysel 2 vir ‘NSC’, ‘ME’ en ‘MRT’. Betekenisvolle verskille het in beide snysels voorgekom vir al die plantproduksie eienskappe. Daar is hoogs betekenisvolle verskille tussen genotipes by snysel 1 getoon vir lewende massatoename/ha volgens al drie inname modelle. Die F1 nageslag van ‘n 6 x 6 halfdialleel kruising is d.m.v. Metode 4, gemengde model B van Griffing (1956b) vir kombineervermoë ontleed, omdat daar slegs een waarde per perseel vir elke eienskap beskikbaar was. By die ontleding van kombineervermoë vir voedingswaarde eienskappe in die F1 nageslag, is betekenisvolle verskille t.o.v. algemene kombineervermoë effekte vir ‘EE’ en al die veseleienskappe behalwe hemi-sellulose en ru-sellulose by snysel 1 getoon. Betekenisvolle verskille is vir ‘EE’, ‘IVDOM’, ‘ME’ en ‘MRT’ by snysel 2 getoon. Betekenisvolle verskille het slegs by snysel 1 vir al die plantproduksie eienskappe voorgekom. Hoogs betekenisvolle verskille is in die geval van snysel 1 getoon vir lewende massatoename/ha volgens al drie inname modelle. Die waardes wat verkry is vir heterose volgens die beter ouer ontledingsmetode was nie goed genoeg om die vorming van basters te regverdig om sodoende lewende massatoename/ha te probeer verhoog nie. Die verhouding tussen die variansie van die algemene kombineervermoë tot die variansie van die spesifieke kombineervermoë asook ‘h2 n’ was matig hoog vir ‘NDFadj’, kg DM/ha en lewende massatoename/ha by snysel 1 en matig vir ‘MRT’ by snysel 2. Hoogs betekenisvolle additiewe genetiese korrelasies is getoon tussen ‘IVDOM’ opbrengs/ha en lewende massatoename/ha volgens al drie inname modelle in die geval van snysel 1 Daar was ‘n betekenisvol negatiewe additiewe genetiese korrelasie tussen kg DM/ha by snysel 1 en ‘IVDOM’ by snysel 2. Aanbevelings is gegee vir die identifikasie van teelouers, die seleksieproses in vroeë generasies asook die finale evaluering om ‘n nuwe kultivar te selekteer vir registrasie.
Thesis (Ph.D. (Plant Sciences: Plant Breeding))--University of the Free State, 2009
Keywords: Triticale; Diallel; Fixed; Nutritive quality; Animal production; Combining; Heritability; Correlation; Triticale -- Breeding -- South Africa; Triticale -- Genetics; Triticale -- Yields